Actual and Potential Trend Analysis Under Climate Change Using Risk Sen's Slope (RSS) in Western Black Sea Basin in Türkiye - Keskin, Muhammed Zakir; Abu Arra, Ahmad; Akca, Seyma; Sisman, Eyuep (WILEY, 2025)
Several classical and innovative trend methods exist in the literature to identify and evaluate the effects of climate change on hydro-meteorological variables. Among the classical methods, the most commonly used ones are modified Mann-Kendall (MMK) and Sen's slope (SS). As for the innovative methods to identify potential trends (probable risk levels) in hydro-meteorological variables depending on changing the initial conditions and temporal dynamic development behaviour of the trends, the risk Sen's slope (RSS) method was proposed based on different risk values. The actual trends are proposed in this research to comprehensively understand and analyse the climate change trend over the entire period. It uses RSS and the classical trends MMK and SS. Also, the spatiotemporal classical, actual and potential trends in meteorological variables are evaluated. Additionally, the advantages of the RSS method compared with classical SS are discussed in detail. The Western Black Sea basin in T & uuml;rkiye, with monthly total precipitation and monthly average temperature data from 1961 to 2023, is selected as a representative application. The temperature trend results show that the 0.99 risk level gave approximately 25% higher slope than SS. The maximum temperature-increasing trend within the study area and the time period at 0.99 risk level is 2.10 degrees C. However, the differences between precipitation trend slopes obtained by SS and RSS for different risk levels are relatively low. Furthermore, using different slopes corresponding to several risk levels allows for more proactive and effective measures for sustainable agricultural activities and water management. The actual temperature trend within the basin ranges between 1.33 degrees C and 2.09 degrees C, and the actual precipitation trend ranges between 2.78 and 12.74 mm over the study period.
Keywords: Mann-Kendall (MK) test; precipitation; risk; temperature; time series; trend; HOMOGENEITY; REGION; Meteorology & Atmospheric Sciences